Spinal cord compression due to brown tumor. Issue 6 (June 2015) - Pikis, Stylianos; Cohen, José E.; Vargas, Andres; Schroeder, Josh; Kaplan, Leon; Itshayek, Eyal
Abstract We report a rare case of a vertebral brown tumor causing spinal cord compression and resulting in progressive paraparesis in a 27-year-old female with end-stage renal failure, managed with hemodialysis. Urgent neurosurgical intervention and gross total resection resulted in complete resolution of the symptoms.